Bimetallic Fe–Co chalcogenophosphates as highly efficient bifunctional electrocatalysts for overall water splitting. (19th January 2021) - Tong, Jinhui; Li, Chunyan; Bo, Lili; Guan, Xiaolin; Wang, Yunxia; Kong, Deyuan; Wang, Huan; Shi, Wenping; Zhang, Yuning
Abstract: Fabrication of multicomponent materials is the most effective strategy to develop high-performance multifunctional catalysts. In this work, a series of bimetallic Fe–Co chalcogenophosphates were facilely prepared and used as bifunctional water electrolysis catalysts. The results have shown that the obtained catalysts showed high performances for hydrogen and oxygen evolution reactions, and overall water splitting. For the optimum catalyst, only 260 and 365 mV of overpotential for HER and OER, and 1.59 V of cell voltage for water splitting was needed respectively in 1 M KOH when 10 mA cm −2 of current density was reached. High stability and Faraday efficiency were also obtained, and the obtained results confirm that the catalyst is competitive in application in water electrolysis. Graphical abstract: A series of bimetallic Fe–Co chalcogenophosphates were facilely prepared and employed as bifunctional water electrolysis catalysts. The optimal sample FCPS-1:2 exhibited highly efficient catalytic activities for HER, OER and overall water splitting. Image 1 Highlights: The preparing procedure is simple. Synergistic effect has been shown for improving the catalytic activity. Doping of P can increase the electron density of the active center. The optimum catalyst has excellent performance in overall water splitting.